Dynamics of pollen release in relation to anther wall structure among species of Solanum (Solanaceae) - Pasarelli, Lilian (2006)
Dynamics of pollen release in relation to anther-wall structure among species of Solanum (sects Brevantherum, Cyphomandropsis and Pachyphylla)were studied. Differences in anther-wall qualities (multi-layered and rigid v. single-layered and ﬂexible) were correlated with shifts between vibratory and pneumatic mechanisms. The species presented different exploitation mechanisms for bees to obtain their pollen. The number of replications (strokes on the bellows and buzzing actions) needed to empty the anthers and the total amount of pollen per ﬂower were signiﬁcantly different among the species. However, the differences were not correlated with differences in structural anther features. The pollination syndrome was related only to the total amount of pollen per ﬂower, which was larger in the pollen ﬂowers.We propose that the pneumatic mechanisms may have played a role simultaneously with the vibratory mechanism as an unclogging device or as a means of increasing male ﬁtness by the pattern of pollen distribution. The pre-existence of the pneumatic principle in pollen ﬂowers must have opened the possibility of pollen deposition on visitors without vibratory capabilities such as a male bee. Parallel to this change a shift in the reward system must have occurred.